Commentary: Economic Concentration and the Antitrust Laws - Victor H. Kramer (Washington University Law Quarterly, 1975)
I propose to review current definitions of monopolization, including some of the newer definitions advanced in the law books and by the Antitrust Division, but not yet adopted by the courts. Then I shall outline the leading proposal for legislative reform of the law of monopolization and venture some personal doubts and questions on the wisdom of the legislation. Next, I shall consider some of the reasons why the Sherman Act has not succeeded in dissolving what has been perceived by many to be excessive or undesirable economic concentration. I shall conclude with some suggestions for a somewhat more workable deconcentration policy for America.
Keywords: Antitrust law